2010 IEEE Second International Conference on Cloud Computing Technology and Science 2010
DOI: 10.1109/cloudcom.2010.21
|View full text |Cite
|
Sign up to set email alerts
|

SafeVanish: An Improved Data Self-Destruction for Protecting Data Privacy

Abstract: In the background of cloud, self-destructing data mainly aims at protecting the data privacy. All the data and its copies will become destructed or unreadable after a user-specified period, without any user intervention. Besides, anyone cannot get the decryption key after timeout, neither the sender nor the receiver. The Washington's Vanish system is a system for selfdestructing data under cloud computing, and it is vulnerable to "hopping attack" and "sniffer attack". We propose a new scheme in this paper, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Although Vanish can achieve data security in such an elegant way, it is not strongly secure due to some special P2Poriented attacks [7], [8]. Another disadvantage of Vanish is the uncontrollable surviving time of the key.…”
Section: Introductionmentioning
confidence: 99%
“…Although Vanish can achieve data security in such an elegant way, it is not strongly secure due to some special P2Poriented attacks [7], [8]. Another disadvantage of Vanish is the uncontrollable surviving time of the key.…”
Section: Introductionmentioning
confidence: 99%
“…Since Vuze automatically deletes the stored data every 8 hours, the data can be self destructed. However, because of Sybil attack and hopping attack, Vanish is not safe, which was shown in [22] and later improved in [23]. Vanish employs the use of DHT to delete data, which takes advantage of the decentralization and large scale features of DHT to provide natural defenses for various attacks.…”
Section: Related Workmentioning
confidence: 99%
“…Research efforts [22] have shown that Vanish is vulnerable to both Sybil attack and hopping attack. Susbequently, the SafeVanish model has been proposed by [25] to increase the cost required to effectively attack the Vanish protocol. Vanish and its similar schemes [15], [24] take significant advantage of the decentralization and large scale features of distributed network to provide natural defense to attacks.…”
Section: Related Workmentioning
confidence: 99%